KRITIK TERHADA P CORPORATE SOCIAL RESPONSIBILITY SEBAGAI STRATEGI KEKUASAAN: SYSTEMATIC LITERATURE REVIEW - Lilik Pujiati; Nur Fadjrih; Wahidahwati; Nur Anisah (STIE PGRI Dewantara Jombang, 2026)
Corporate Social Responsibility (CSR) is widely understood as a form of corporate moral responsibility towards society and the environment. However, from a critical perspective, CSR can be understood not merely as an ethical practice but as an instrument of power that reproduces corporate dominance in the socio-economic order. This conceptual paper aims to examine CSR through a power theory approach, particularly drawing on Michel Foucault's thinking on power relations and discourse, and Antonio Gramsci's on hegemony. The paper's central argument is that CSR functions as a mechanism for legitimizing, normalizing, and depoliticizing structural conflicts between corporations and society. CSR is not merely a practice of philanthropy or regulatory compliance, but rather part of a hegemonic strategy that shapes public perception, manages resistance, and maintains the stability of the global capitalist system. This paper offers a conceptual framework for interpreting CSR as a practice of symbolic and structural power.